Analysis of the Nondeterministic Dynamic Structural Behavior of a Steel Wind Tower when Subjected to Wind Loadings - da Silva Castilho, Andre Victor; Guedes Simoes, Rodrigo; Machado de Oliveira, Leandro Rocha; Cunha Pires Soeiro, Francisco Jose; Santos da Silva, Jose Guilherme (Engineering, Technology & Applied Science Research, 2025)
This study presents an in-depth investigation into the structural dynamics response of a wind tower designed to support a 2 MW onshore wind turbine. The tower’s finite element model was developed using the Finite Element Method (FEM), utilizing the ANSYS software and considering the wind loadings on the rotor and tower and the effect of the geometric nonlinearities and soil-structure interaction, aiming to obtain a realistic representation of the structure’s dynamic behavior. The stochastic nature of the wind loadings was considered, and a statistical analysis was carried out on the structure’s dynamic responses. Then, an extensive parametric study was performed, considering several basic wind velocities to assess the steel tower’s dynamic structural behavior based on horizontal displacements, von Mises stresses, and the fatigue service life. The results showed that within the operational limit of the turbine, the investigated tower complies with the recommended limits specified in the current wind tower design standards. However, for higher basic wind speeds, the wind tower’s structural design does not meet these requirements.